Emergency room endotracheal intubation in children with bronchiolitis: A cohort study using a multicenter database. Issue 3 (30th June 2020) - Carter, Marla R.; Khan, Aamer H.; Salman, Tarek; Speicher, Richard; Rotta, Alexandre T.; Shein, Steven L.
Abstract: Background and Aims: Bronchiolitis and asthma have a clinical overlap, and it has been shown that pediatric intensive care unit (PICU) patients with asthma undergoing endotracheal intubation in a community hospital emergency room (ER) have a shorter duration of mechanical ventilation (MV) and PICU length of stay (LOS) vs children undergoing intubation in a children's hospital. We aimed to determine if the setting of intubation (community vs children's hospital ER) is associated with the duration of MV and PICU LOS among children with bronchiolitis. Methods: With IRB approval, data in the Virtual Pediatric Systems (VPS, LLC) database were queried for bronchiolitis patients <24 months of age admitted to one of 103 predominantly North American PICUs between 1/2009 and 1/2016 who had an endotracheal tube in place at PICU admission. There were no exclusion criteria. Extracted data included ER type (community/external or children's hospital/internal), demographics, and reported comorbidities. Outcomes analyzed were duration of MV and PICU LOS. Multivariable linear regression was used to evaluate if intubation location was independently associated with the outcomes of interest. Results: Among 1934 patients, median age was 2.0 (IQR: 1.0‐4.8) months, 51% were admitted from an external ER, 41% were White, 61% were male, and 28% had ≥1 comorbidity. Median duration of MV was 6.6 (4.6‐9.5) days and the median PICU LOS was 7.0 (4.6‐10.6) days. Children who underwent endotracheal intubation in a children's hospital ER had a modestly longer duration of MV (6.7 [4.4‐9.4] vs 6.5 [5.2‐9.6] days, P < .001, Mann‐Whitney U ) and longer PICU LOS (7.2 [4.8‐10.8] vs 6.9 [4.2‐10.1] days, P = .004, Mann‐Whitney U ). After adjusting for confounding variables, we did not observe a significant association between the location of endotracheal intubation and duration of MV or PICU LOS. Conclusion: In this cohort, and unlike outcomes of near‐fatal asthma, we observed that clinical outcomes of critical bronchiolitis were similar regardless of location of endotracheal intubation.